A Systematic Review of Research on Blended Learning in Teaching EFL: Student and Teacher’s Perception, Implementation, Interaction, Benefits, and Challenges - Koniah, Musfi Kotul; Putri, Rizkia Aura; Anindita, Shafinaz Aulia; Masayu, Zakia Reeva (STAIRS: English Language Education Journal, 2024)
Blended learning is widely implemented in EFL classrooms, with research highlighting its benefits for students and teachers, yet challenges in perception, interaction, and implementation remain underexplored. While studies acknowledge its positive impact, gaps persist in understanding its long-term effectiveness and the factors influencing successful adoption. This study examines the existing research on blended learning in English as a Foreign Language (EFL) classrooms, focusing on the views and experiences of both students and teachers. An analysis of 30 published articles reveals that researchers have employed a range of methods, including quantitative, qualitative, and mixed approaches, to collect data through questionnaires, interviews, and literature reviews. The findings suggest that both students and teachers have a positive outlook on blended learning, which is used to teach various English skills and involves the use of online platforms to assign different types of tasks. Effective interaction between students, teachers, and peers is crucial to the success of blended learning. The benefits of blended learning include improved English proficiency, enhanced learning behaviors, and developed digital skills. However, challenges such as technical difficulties, inadequate training, time management issues, and learner preparedness can hinder its implementation.